EFFECT OF ELECTRODE DISTANCE AND VOLTAGE ON CR, COD, and TSS REDUCTION IN WASTE WATER TANNING INDUSTRY USING ELECTROCOAGULATOR BATCH - Setyawati, Harimbi; Galuh, Dinda; Yunita, Erni (Journal of Sustainable Technology and Applied Science (JSTAS), 2021)
Wastewater from the tanning industry has relatively high Cr, COD, and TSS metal pollutants. According to the regulation of the Minister of Environment of the Republic of Indonesia No. 5 of 2014 concerning the quality standard of wastewater for industrial activities, the standard quality value is 0.6 mg/L of Cr, 110 mg/L of COD, and 60 mg/L of TSS. This research aimed to determine the effect of electrode distance and voltage on reducing Cr, COD, and TSS levels in the wastewater from the tanning industry using batch electrocoagulation. The electrocoagulation method used in this research with fixed variables was the number of 2 plate electrodes and the changing variables; it was the distance between the electrodes (1, 1.5, 2, 2.5 and 3 cm) and the electric voltage (3, 6 and 9 volts). The research was conducted on a laboratory scale in batches with a capacity of 10 litres. The electrodes used were aluminium (Al) as the anode and the cathode in plates. The analysis showed that the highest percentage reduction in COD reached 88.8889% and the highest Cr reached 83.4712% occurred at a distance of 2 cm with 9 volts voltage, the highest percentage reduction in TSS reached 85.0746% with a distance of 3 cm with 9 volts voltage. From the results of this research, it could be concluded that the electrocoagulation method in the batch electrocoagulator was efficient enough to reduce the levels of Cr, COD, and TSS with variable electrode distance and electric voltage.